2016
DOI: 10.1038/ng.3528
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of five chronic inflammatory diseases identifies 27 new associations and highlights disease-specific patterns at shared loci

Abstract: We simultaneously investigated the genetic landscape of ankylosing spondylitis, Crohn's disease, psoriasis, primary sclerosing cholangitis and ulcerative colitis to investigate pleiotropy and the relationship between these clinically related diseases. Using high-density genotype data from more than 86,000 individuals of European-ancestry we identified 244 independent multi-disease signals including 27 novel genome-wide significant susceptibility loci and 3 unreported shared risk loci. Complex pleiotropy was su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
603
0
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 667 publications
(623 citation statements)
references
References 55 publications
14
603
0
6
Order By: Relevance
“…[20][21][22] In the case of auto-immune diseases, evidence implies that at some loci, the same causal variants are driving the observations of associations across diseases. [23][24][25] Fourth, analytical methods that estimate genetic correlations from GWAS data have provided evidence for widespread pleiotropy. 20,26 The corollary of pervasive pleiotropy for complex traits is that the paradigm of ''one gene, one function, one trait'' is the wrong way to view genetic variation in the human genome (and the same applies for studying disease in experimental organisms).…”
Section: Pleiotropy Is Pervasivementioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22] In the case of auto-immune diseases, evidence implies that at some loci, the same causal variants are driving the observations of associations across diseases. [23][24][25] Fourth, analytical methods that estimate genetic correlations from GWAS data have provided evidence for widespread pleiotropy. 20,26 The corollary of pervasive pleiotropy for complex traits is that the paradigm of ''one gene, one function, one trait'' is the wrong way to view genetic variation in the human genome (and the same applies for studying disease in experimental organisms).…”
Section: Pleiotropy Is Pervasivementioning
confidence: 99%
“…A recent cross-disease study involving the conditions ankylosing spondylitis (AS [MIM: 106300]), inflammatory bowel disease (IBD [MIM: 266600]), primary sclerosing cholangitis (MIM: 613806), and psoriasis identified without any further genotyping 30 new loci at genome-wide significance. 24 Transethnic studies have demonstrated substantial genetic overlap between ethnically remote populations; 106 109 The SNP leads to loss of the transmembrane domain of the receptor, and the risk SNP for MS (protective for AS) leads to increased serum soluble TNF receptor. 110 TNF inhibition, including by decoy TNF receptor therapies, is highly effective for AS and many other immune-mediated diseases, but its use can be complicated by de novo development of MS, and in MS itself, it can exacerbate disease.…”
Section: Type 2 Diabetesmentioning
confidence: 99%
“…Such pleiotropic variants are particularly interesting, as the functional impact of a SNP on one or several genes may provide clues about the underlying molecular mechanism. For example, a significant overlap of shared genetic variants and pathways has been detected in immune-mediated diseases, suggesting extensive pleiotropic effects [6][7][8]. These shared genetics variants linked to pathways are ideally suited to identify candidate mechanisms underlying a "shared aetiology" of different diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) have identified several other genes other than HLA-B*27 are associated with AS pathology including IL23R, TYK2, JAK2, STAT3 and IL12B (encodes for IL-12p40 subunit) suggest the importance of IL-23 signalling in AS pathology (Cortes et al, 2015, Ellinghaus et al, 2016, International Genetics of Ankylosing Spondylitis et al, 2013. Given the importance of IL-23 in maintaining memory Th17 cells (Wilson et al, 2007), these studies implicated that IL-23-Th17 axis in AS pathology.…”
Section: ) Ankylosing Spondylitis (As)mentioning
confidence: 99%
“…GWAS have identified several other genes other than HLA-B*27 are associated with AS pathology including IL23R, TYK2, JAK2, STAT3 and IL12B (encodes for IL-12p40 subunit) suggest the importance of IL-23 signalling in AS pathology (Cortes et al, 2015, Ellinghaus et al, 2016, International Genetics of Ankylosing Spondylitis et al, 2013. Furthermore, a proof-of-concept clinical trial of ustekinumab (IL-12p40 neutralising monoclonal antibody) was recently conducted and demonstrated effectiveness in AS patients (Poddubnyy et al, 2014).…”
Section: ) Introductionmentioning
confidence: 99%